Digital Mental Health Innovation: Effectiveness of Qolbu Care App in Reducing Anxiety and Improving Resilience among Adolescents in Disaster-Prone Areas - Nurul Hidayah; Florensa; Nisma; Muhammad Luthfi; Yogasliana Fathudin (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
High levels of anxiety and low resilience remain common psychological challenges faced by individuals in coping with life stressors. Technology-based approaches, such as mental health applications, offer innovative and easily accessible solutions, yet remain under-researched in Indonesia.  This study aims to analyze the Qolbu Care application’s effectiveness on respondents' anxiety and resilience levels. The research employed a quasi-experimental design with a one-group pretest–posttest approach involving 90 respondents. The intervention was administered over eight weeks using the Qolbu Care application. Standardized anxiety and resilience questionnaires were used as research instruments. Data were analyzed using a paired t-test. The analysis revealed a statistically significant reduction in anxiety levels (mean = –16.45; SD = 8.12; SE = 1.05; p = 0.0001), as well as a statistically significant increase in resilience (mean = 11.40; SD = 6.85; SE = 0.98; p = 0.0001). The Qolbu Care application has proven effective in reducing anxiety and enhancing resilience among respondents. These findings affirm that digital-based interventions can be an innovative alternative for psychosocial support within nursing practice.